A Robertsonian translocation from Thinopyrum bessarabicum into bread wheat confers high iron and zinc contents. Issue 3 (18th March 2016) - Ardalani, Somayeh; Mirzaghaderi, Ghader; Badakhshan, Hedyeh
Abstract: Development of wheat–alien translocation lines has facilitated practical utilization of alien species in wheat improvement. The production of a compensating Triticum aestivum – Thinopyrum bessarabicum whole‐arm Robertsonian translocation (RobT) involving chromosomes 6D of wheat and 6E b of Th. bessarabicum (2n = 2 x = 14, E b E b ) through the mechanism of centric breakage–fusion is reported here. An F2 population was derived from plants double‐monosomic for chromosome 6D and 6E b from crosses between a DS6E b (6D) substitution line and bread wheat cultivar 'Roushan' (2n = 6 x = 42, AABBDD) as female parent. Eighty F2 genotypes (L1–L80) were screened for chromosome composition. Three PCR‐based Landmark Unique Gene (PLUG) markers specific to chromosomes 6D and 6E b were used for screening the F2 plants. One plant with a T6E b S.6DL centric fusion (RobT) was identified. A homozygous translocation line with full fertility was recovered among F3 families and verified with genomic in situ hybridization (GISH). Grain micronutrient analysis showed that the DS6E b (6D) substitution line and T6E b S.6DL stock have higher Fe and Zn contents than the recipient wheat cultivar 'Roushan'.